Ecological restoration through a phylogenetic perspective - Azevedo, Bruna Pereira de (2021)
Ecological restoration of ecosystems is seeing as the path to mitigate and reverse the currently scenario of biodiversity and ecosystem services losses. The science of ecological restoration, known as restoration ecology, grew rapidly over the years and is currently an interdisciplinary field that covers several areas of knowledge and seeks to outline restoration methodologies and strategies to achieve results that are significant for both nature and humans. Among the many disciplines that can contribute to restoration ecology one, specifically, is slowly gaining attention: phylogenetics. Phylogenetics is the field of biology focused in understanding the degrees of phylogenetic relationships among a given group of organisms. Since the 90s, these relationships were incorporated as measures of community diversity within the phylogenetic diversity metrics. This dissertation aims to look at ecological restoration through a phylogenetic perspective. In the first chapter, we performed a systematic review in order to identify the trends and gaps of phylogenetic studies in restoration ecology of terrestrial vegetation. Acknowledging the absence of phylogenetic studies in the neotropics we present, in the second chapter, the first large scale assessment of phylogenetic diversity in tropical forests restorations and discuss the level of evolutionary recovery in such highly diverse ecosystem.